2D stiffness mapping for localizing osteoarthritic degenerated cartilage by using a fast indentation system based on fiber Bragg gratings - Kalahrodi, A. Javadzadeh; Marchi, G.; Moeller, J.; Nolte, Stefan; Roths, Johannes (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
A fast indentation system for 2D stiffness mapping of cartilage is presented. The goal of this technique, which has the potential to be deployed endoscopically, is to localize and to distinguish between regions of healthy and degenerated cartilage. In the system presented here, forces are measured by a fiber Bragg grating (FBG), which is located at the end of a fiber optic indenter probe. This approach enables small indenter dimensions, which are advantageous for endoscopic use. Differences between the stiffness parameters measured on healthy cartilage and on the same sample after artificial degeneration are observed. It is shown that the fast indentation system has the capability to distinguish healthy bovine cartilage from artificially degenerated one. The evaluation of this capability will make the conclusions of the work.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Biomechanics of cartilage; Fast indentation; Fiber Bragg grating; Optical biosensor